Performance Evaluation and Strategy of Small and Medium-Sized Business in Manado City Shopping Center - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 5 No.1, 2006 JBE UNKLAB, 2006)
This research aims to evaluate the performance and strategy of small and medium-sized business in Manado City Shopping Center. Data were collected from 96 business, with the goal of evaluating 1. The extent to which business owners implement business strategy in terms of: a. Managerial, b. Financial, c. Credit, d. Production, e. Marketing, and f. Worker aspects; 2. Performance of business owners in related to those aspects; 3. Problems encountered by the business owneer related to those aspects; and 4. What could be the solution to the problems. The six aspects represent important strategy factors used to evaluate performance of entrepreneurs in small and medium-zised business. This may signify critical key success factors to the businesses in their growing process. Results from the sample 96 business indicate that majority of entrepreneurs still young in age of less than 30 years and only very few of them college graduates. There were no good financial system and procedures practiced. Bank credit is really needed, but generally could not be received timely and as needed. The business could not afford to buy technology needed to improveproduction quality. Trade exhibitions perceived as expense only instead of investment and these events are still rarely done in Manado. Workers in this business work hard, seriously and skillful but the productivity has not maximum and communications with customers normally dine in local language. Products and sevices offered buy these businesses are still for local market only. To make it more challenging and interesting, cooperation with large businesess with assistants of government in the program of management, marketing and production techniques will be verry helpful.